Construction waste management methods used by contractors in the Northern Region / Siti Hafizan Hassan … [et al.] - Hassan, Siti Hafizan (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2009)
The construction industry produces a significant amount of building waste. The government is taking action to tackle the problem, such as by introducing a construction waste landfill charge, and promoting prefabrication to reduce onsite waste generation. This paper reports an ongoing study on the use of construction waste management methods by contractor and its impact on waste reduction in the Northern Region. A questionnaire survey was administered to experienced professionals, such as main contractors, subcontractors, and consultancy agencies. The results revealed that construction waste reduction is one of the major benefits when emphasizing on the sizing and amount of materials to be ordered in reducing wastage with the mean response of normally practiced toward mostly practiced. Source reduction by accurate estimating and ordering of materials are the methods that are mostly used by industry participants in minimizing construction waste. But when there are wastes, the respondents prefer to reuse, burn or land fill as the methods for disposing construction waste at their sites. This implies that contractors in the Northern Region try to reduce their construction wastes at the very earliest stage in construction but they like to use burning as a method of disposing which is not good for the environment.